2020
DOI: 10.26789/aeb.2020.01.003
|View full text |Cite
|
Sign up to set email alerts
|

Comparative response of SOD in different plants against cadmium and drought stress at the molecular level

Abstract: Abiotic stress like drought and heavy metal imposes a negative impact on exposed plants’ growth and development, commences over production of reactive oxygen species (ROS) inside plant cells resulting in oxidative stress at the cellular level. After that, plants activate multiple defense mechanisms, within which the superoxide dismutase (SOD) family acts as the first line of defense to eliminate ROS. From the literature, it is evident that fewer studies have been carried out in combination with molecular evolu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 48 publications
2
2
0
Order By: Relevance
“…The findings revealed that the OjSOD genes in roots were responsive to various heavy metal stresses, with Cu/ZnSOD-15, Cu/ZnSOD-18, and Cu/ZnSOD-22 exhibiting significantly increased expression levels ( Figure 8 ). This aligns with prior research findings in rice, which reported that the expression of OsCu/ZnSOD-3 was markedly increased in response to Cd stress, serving as a defense mechanism against the toxic effects of Cd ( Yang et al., 2020 ). Similarly, Liu et al.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The findings revealed that the OjSOD genes in roots were responsive to various heavy metal stresses, with Cu/ZnSOD-15, Cu/ZnSOD-18, and Cu/ZnSOD-22 exhibiting significantly increased expression levels ( Figure 8 ). This aligns with prior research findings in rice, which reported that the expression of OsCu/ZnSOD-3 was markedly increased in response to Cd stress, serving as a defense mechanism against the toxic effects of Cd ( Yang et al., 2020 ). Similarly, Liu et al.…”
Section: Discussionsupporting
confidence: 91%
“…This categorization aligns with the classifications in Nicotiana tabacum (Huo et al, 2022), Salvia miltiorrhiza (Han et al, 2020), soybeans (Aleem et al, 2022), Daucus carota (Zameer et al, 2022), potato Hou et al 10.3389/fpls.2024.1355849 Frontiers in Plant Science frontiersin.org (Rudićet al, 2022), and wheat (Tounsi et al, 2023) 8). This aligns with prior research findings in rice, which reported that the expression of OsCu/ZnSOD-3 was markedly increased in response to Cd stress, serving as a defense mechanism against the toxic effects of Cd (Yang et al, 2020). Similarly, Liu et al found a notable increase in the expression of Cu/ZnSOD under Cd treatment in rice (Liu et al, 2023).…”
Section: Discussionsupporting
confidence: 90%
“…ROS are byproducts of aerobic metabolism (Sies et al, 2022;Jadhav et al, 2011). Under normal conditions, the production and scavenging of intracellular ROS are in dynamic balance (Yan et al, 2022;Yu et al, 2020). The results presented this study showed that the ROS and the MDA content in GXM increased significantly when the NH + 4 concentration was 67.30 mg L −1 .…”
Section: Discussionmentioning
confidence: 68%
“…Gokul et al [ 68 ] found that SOD activity affected the heavy metal stress tolerance of Brassica napus. Yu et al [ 69 ] revealed the function of SOD in the interaction between plants and abiotic stress, and SOD played an important role in plants’ tolerance to Cd stress. At present, SOD has been widely studied in the neighborhood where plants tolerate abiotic stress.…”
Section: Discussionmentioning
confidence: 99%